Abreviasi dalam Berita Utama Surat Kabar Harian Singgalang Periode Juli-Desember 2023 - Sefrianto, Remon; Manaf, Ngusman Abdul (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to find and describe the types and processes of forming abbreviations contained in the headlines of the Singgalang newspaper for the period July-December 2023. This study is a type of qualitative research with a descriptive method. The data for this study were randomly selected that met the requirements as abbreviations in the uploads from June 2023 to December 2023. The source of this research data is from the uploads of the Singgalang newspaper on the website www. Harian Singgalang.co.id. The methods and techniques for collecting data in this study are to carry out several stages, first, a literature study is used to obtain references to support the research. Second, data search or observation on the uploads of the Harian Singgalang newspaper. Third, collect all data in table form. The data validation technique for this study is the triangulation technique. Based on the research data found, the results of this study are as follows. First, the data obtained based on the research conducted in the headlines of the Singgalang daily newspaper contains data in the form of types of abbreviations and the process of forming abbreviations. In total, there are 95 data in the Singgalang newspaper which are abbreviations. Based on the type, the abbreviations consist of 59 abbreviation data in the form of abbreviations, 7 abbreviation data in the form of excerpts, 8 abbreviation data in the form of acronyms, 17 abbreviation data in the form of contractions, and 4 data in the form of letter symbols. Furthermore, the process of forming the abbreviations found in the headlines of the Singgalang newspaper for the period July-December 2023 is 95 data. with details, 61 data in the form of letter preservation, 8 data in the form of word preservation, 8 data in the form of letter and number preservation, 14 data in the form of letter and syllable preservation, and 2 data in the form of syllable and word preservation.